Inflation forecasts: Are market-based and survey-based measures informative? - Magdalena Grothe; Aidan Meyler (European Central Bank (ECB), 2015)
This paper analyses the predictive power of market-based and survey-based inflation expectations for actual inflation. We use the data on inflation swaps and the forecasts from the Survey of Professional Forecasters for the euro area and United States. The results show that both, market-based and survey-based measures have a non-negligible predictive power for inflation developments, as compared to statistical benchmark models. Therefore, for horizons of one and two years ahead, market-based and survey-based inflation expectations actually convey information on future inflation developments.
Keywords: E31; E37; G13; 330; inflation expectations; inflation forecasting; inflation swap markets; market-based inflation expectations; Survey of Professional Forecasters; survey-based inflation expectations